Investigating the performance of asset pricing models in different economic and interest rate using individual dan portfolio stock return - , Wihartanto Raharjo, Prof. Dr. Indra Wijaya Kusuma, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study is aimed at testing the performance of asset pricing models, including the Capital Asset Pricing Model (CAPM) and the Fama French Three- Factors (FF3F model), while economic condition and interest rate is changing by using individual and portfolio stockâs return in Indonesia capital market. To do so, this study first tests the performance of CAPM and FF3F model by using individual and portfolio stockâs return data. Then, it investigates the performance and stability of two modelsâ parameters while economic condition and interest rate is changing. This research examines non-financial institutions with positive book-tomarket ratio and finally 160 companiesâ stocks are observed from January 2002 to December 2011. The time series regression is performed to test the performance and the stability of two models, the CAPM and the FF3F model. There are mainly three results of this research. First, the FF3F model is more superior than CAPM when it is tested in explaining the portfolio return, but the FF3F model is only marginally better than the CAPM when it is tested in explaining the individual stock return. Second, at different economic condition (bull/bear market period), the study finds that the FF3F model is more superior than CAPM when it is tested to the portfolio, but when it is tested to the individual stock it does not work, as well. However, both two models do not show sufficient stability of parameters, including Î², s, and h. Finally, the similar results are obtained when both two models are tested in different interest rate period (increasing/decreasing period). These results are different from the previous research showing that the coefficient of excess market return (Î²) is more stable than two other parameters, s and h, added in the FF3F model.